2018
DOI: 10.1186/s13634-018-0560-x
|View full text |Cite
|
Sign up to set email alerts
|

Locally optimal detector design in impulsive noise with unknown distribution

Abstract: This paper designs the locally optimal detector (LOD) in additive white impulsive noise with unknown distribution. Unlike traditional LODs derived from a known or approximated noise probability density function (PDF), the LOD proposed in this paper is achieved by designing the zero-memory non-linearity (ZMNL) function based on real data. After the PDF estimation in a nonparametric way by a kernel method, the ZMNL function is designed as a piecewise differentiable function consisting of a polynomial function an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…T and σ, to improve the detection performance of the GZMNL in SαS noise. To test the optimality of non‐linear function, the efficacy function is used by scriptEα,γfalse(T,σfalse)=GT,σ(x)fα,γ(x)normaldx2normal∞normal∞GT,σ2false(xfalse)fα,γfalse(xfalse)thinmathspacedx.The efficacy is closely related to the detection performances, as proved in [8, 9].…”
Section: Optimisation Design Of the Gzmnlmentioning
confidence: 99%
See 2 more Smart Citations
“…T and σ, to improve the detection performance of the GZMNL in SαS noise. To test the optimality of non‐linear function, the efficacy function is used by scriptEα,γfalse(T,σfalse)=GT,σ(x)fα,γ(x)normaldx2normal∞normal∞GT,σ2false(xfalse)fα,γfalse(xfalse)thinmathspacedx.The efficacy is closely related to the detection performances, as proved in [8, 9].…”
Section: Optimisation Design Of the Gzmnlmentioning
confidence: 99%
“…The efficacy is closely related to the detection performances, as proved in [8,9]. The optimal parameters should make the GZMNL achieve the maximum efficacy.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, the algebraic-tailed ZMNL (AZMNL) can approximate the LOD nonlinearity of the SαS distribution better than the blanker [26]. Our previous work has analyzed the ZMNL designs based on algebraic tail [33] and Gaussianization [34], both of which are only sub-optimal compared to the LOD. It is demonstrated that the match between tails and distributions is essential for nonlinearity in impulsive noise.…”
Section: Introductionmentioning
confidence: 99%
“…In recent two decades, there has been great interest in studying the symmetric α‐ stable false(SαSfalse) distribution, which has been tested to match the real impulsive noise [3–5]. The locally optimum detector (LOD) is of much interest since it is optimal in detecting weak signals from Neyman–Pearson lemma [6–10]. However, the LOD requires an explicit form for the noise probability density function (PDF), and therefore, cannot be implemented in the case of SαS noise for there are no closed forms for the PDF of the SαS noise, except for two special cases (Gaussian and Cauchy distribution).…”
Section: Introductionmentioning
confidence: 99%